1995
DOI: 10.2307/2269349
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Pastoralists on Woodlands in South Turkana, Kenya: Livestock‐ Mediated Tree Recruitment

Abstract: Since the turn of the century, African pastoralists have been held responsible for overuse of woody plants and for the degradation and desertification of many arid and semiarid lands. We analyzed the impacts of pastoral nomads and their livestock on the recruitment (establishment to first reproduction) of Acacia tortilis, a dominant tree in the dry woodlands of South Turkana, Kenya, where Acacia seedpods make up an important part of livestock diets. Seed density averaged over 85 times higher in bush‐fenced liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 51 publications
8
109
0
Order By: Relevance
“…Augustine (2003) found that bomas that had recently been abandoned (1-5 years) had higher total soil N than the areas which had been abandoned for longer periods and therefore attributed the increased N to be from manure and urine inputs during the time the areas were actively used as bomas. Reid and Ellis (1995) reported that soils from abandoned bomas contained ninefold more total C and threefold more total N than adjacent control soils and that these elevated concentrations of C and N in bomas remained for up to 20 years following abandonment. This difference in total C and N accumulation in bomas is due to the fact that the majority of the areas surrounding bomas are nutrient poor and do not support much biomass production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Augustine (2003) found that bomas that had recently been abandoned (1-5 years) had higher total soil N than the areas which had been abandoned for longer periods and therefore attributed the increased N to be from manure and urine inputs during the time the areas were actively used as bomas. Reid and Ellis (1995) reported that soils from abandoned bomas contained ninefold more total C and threefold more total N than adjacent control soils and that these elevated concentrations of C and N in bomas remained for up to 20 years following abandonment. This difference in total C and N accumulation in bomas is due to the fact that the majority of the areas surrounding bomas are nutrient poor and do not support much biomass production.…”
Section: Resultsmentioning
confidence: 99%
“…In East Africa, the study of Bbomas[ (enclosures for cattle protection), which are the equivalent of bedding areas, has shown that, following abandonment, bomas often support a unique plant community and potentially alter the spatial pattern of nutrient cycling within the ecosystem (Augustine, 2003). In Northern Kenya, old bomas contained sixfold to ninefold more soil nitrogen (N) and phosphorus (P) than surrounding habitats and supported thickets of regenerating Acacia tortilis (Reid and Ellis, 1995). In southern Kenya, abandoned bomas were dominated by a lawn of Cynodon nlemfuensis, with enriched concentrations of nutrients both in soils and grasses (Stelfox, 1986).…”
mentioning
confidence: 99%
“…In some cases, adjacent grazing areas are rotated in the same season as well (Niamir-Fuller 1998). Variations of this pattern, involving the rotation of herd animal enclosures, may result in landscape-level management in the long term through the production of islands of Acacia, a keystone species, by providing nutrient-rich microhabitats suitable for the growth of this tree species (Reid and Ellis 1995).…”
Section: Practices Largely Abandoned By Conventional Resource Managemmentioning
confidence: 99%
“…These land demands are controlled by biophysical and socio-economic factors, but also compete for limited space. The transition between forest͞ woodlands and grasslands is driven largely by edaphic factors and disturbances such as fires, heavy browsing by elephants, and natural succession (33)(34)(35)(36)(37), although many of these processes have underlying human drivers (38,39). Foremost among these is land conversion to agriculture (ref.…”
Section: Conceptual Modelmentioning
confidence: 99%